On Race and Time. (November 2015) - Moskowitz, Gordon B.; Olcaysoy Okten, Irmak; Gooch, Cynthia M.
Arousal is known to shape time perception, and heightened arousal causes one to perceive that time has slowed (i.e., a given length of time feels longer than it actually is). The current experiments illustrate that among White people who experience arousal when contemplating race (specifically those for whom appearing biased is an ongoing concern), time perception slows when they observe faces of Black men. We asked participants to judge the duration of presentation for faces of White and Black men (shown for periods ranging from 300 to 1, 200 ms) relative to a standard duration of 600 ms. Evidence of bias emerged when White participants concerned with bias saw faces of Black men (e.g., durations of less than 600 ms were perceived as being greater than 600 ms). The current findings have implications for intergroup interactions in which timing is essential—for example, length of job interviews, police officers' perception of the length of an encounter and when force should be initiated, and doctors' perception of the length of medical encounters. Racially biased time perception is a new form of implicit bias, one exerted at the perceptual level.